2016
DOI: 10.1177/1367006916681080
|View full text |Cite
|
Sign up to set email alerts
|

Is there a bilingual advantage in phonetic and phonological acquisition? The initial learning of word-final coronal stop realization in a novel accent of English

Abstract: Research question:We address the question of whether the cognitive advantage of the bilingual mind, already demonstrated in the case of auditory processing or novel word acquisition, also applies to other linguistic domains, specifically to phonetic and phonological learning. Design:We compare the performance of 17 monolinguals and 25 bilinguals from Canada in a production experiment with two tasks: imitation and spontaneous reproduction of a novel foreign accent, specifically Sussex English. Data and analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 75 publications
2
14
0
Order By: Relevance
“…Early bilinguals, on the other hand, may be able to utilize phonological working memory resources more efficiently to learn even non-native-like words. Recall that Spinu and colleagues [ 131 ] proposed a similar hypothesis, suggesting that more robust subcortical sound encoding could increase the availability of acoustic signals in auditory sensory memory. This could in turn allow for more effective recruitment of phonological working memory, facilitating discrimination of unfamiliar phonetic contrasts, and potentially, the acquisition of novel vocabulary.…”
Section: Language Learningmentioning
confidence: 96%
See 1 more Smart Citation
“…Early bilinguals, on the other hand, may be able to utilize phonological working memory resources more efficiently to learn even non-native-like words. Recall that Spinu and colleagues [ 131 ] proposed a similar hypothesis, suggesting that more robust subcortical sound encoding could increase the availability of acoustic signals in auditory sensory memory. This could in turn allow for more effective recruitment of phonological working memory, facilitating discrimination of unfamiliar phonetic contrasts, and potentially, the acquisition of novel vocabulary.…”
Section: Language Learningmentioning
confidence: 96%
“…In addition to better discrimination of non-native contrasts during comprehension, bilingualism may confer advantages for the production of novel sounds. For example, Spinu et al [ 131 ] recently found that after training, bilinguals were better able to reproduce a non-native Sussex English accent (as measured by the glottal-stop rate) compared to monolinguals. The authors conjecture that this bilingual advantage for phonological acquisition may be related to their more robust encoding of speech sounds at the level of the brainstem.…”
Section: Speech Perception and Productionmentioning
confidence: 99%
“…Tremblay and Sabourin (2012) extended these findings: not only did bilinguals outperform monolinguals, but multilinguals outperformed bilinguals. Spinu et al (2018) also found a bilingual advantage in learning the sound pattern of a novel dialect, and proposes that it might spring from the fact that bilinguals show enhanced subcortical encoding of sound, relative to monolinguals (Krizman et al, 2012). If bilinguals are at an advantage in encoding and learning new sounds, they may also have an advantage in encoding and learning new sound patterns.…”
Section: Discussionmentioning
confidence: 97%
“…Phonetic imitation is a complex behavior, requiring accurate perception, identification, and (re-) production of the relevant characteristics of the target of imitation. Previous work has shown that listeners are sensitive to, and can to some extent spontaneously reproduce, phonetic properties of familiar accents when asked to mimic them from memory (e.g., Flege and Hammond, 1982;Mora et al, 2014), and that they can imitate properties of novel (D'Imperio et al, 2014;Spinu et al, 2018) or artificial (Spinu et al, 2020) accents, or phonetic variation in words or syllables (Olmstead et al, 2013;Dufour & Nguyen, 2013). The variability found within these studies reflects the wide range of imitative ability in the real world.…”
Section: Introductionmentioning
confidence: 93%
“…Mandarin, 1 Portuguese, 3 Spanish, 2 Tagalog). 3 Our recruitment target, based on an a priori power 3 As suggested in previous work (Spinu et al, 2018), bilinguals may have better imitative ability, and we might in particular expect that participants with short-lag voiceless stops in their native inventory (e.g., Spanish, Portuguese, Tagalog) might be better at imitating shortened VOTs than English monolingual speakers. We conducted exploratory analyses to see whether the 6 participants who fit this profile showed different patterns in either perception or production: specifically, we coded participants as multilingual (i.e., these 6 participants) or monolingual and tested whether the effect of this factor was significant in any of the statistical models.…”
Section: Participantsmentioning
confidence: 99%